1995
DOI: 10.1073/pnas.92.16.7167
|View full text |Cite
|
Sign up to set email alerts
|

The CuA center of cytochrome-c oxidase: electronic structure and spectra of models compared to the properties of CuA domains.

Abstract: The electronic structure and spectrum of several models of the binuclear metal site in soluble CuA domains of cytochrome-c oxidase have been calculated by the use of an extended version of the complete neglect of differential overlap/spectroscopic method. The experimental spectra have two strong transitions of nearly equal intensity around 500 nm and a near-IR transition close to 800 nm. The model that best reproduces these features consists of a dimer of two blue (type 1) copper centers, in which each Cu atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…Comparing a valence-localized dimer with a valence-delocalized dimer, n is expected to be halved whereas Δr is expected to be doubled (n mon /n dim ∼ 0.5 and Δr mon / Δr dim ∼ 2), so λ i should be roughly twice as large for a localized oxidation process, assuming similar force constants (46)(47)(48). The DFT calculated values of λ i (1b) are in agreement with this prediction, with a reorganization energy for a charge-localized cubane twice that of a charge-delocalized cubane.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing a valence-localized dimer with a valence-delocalized dimer, n is expected to be halved whereas Δr is expected to be doubled (n mon /n dim ∼ 0.5 and Δr mon / Δr dim ∼ 2), so λ i should be roughly twice as large for a localized oxidation process, assuming similar force constants (46)(47)(48). The DFT calculated values of λ i (1b) are in agreement with this prediction, with a reorganization energy for a charge-localized cubane twice that of a charge-delocalized cubane.…”
Section: Resultsmentioning
confidence: 99%
“…At pH 7.0 it exhibits two strong absorbance maxima at 482 nm and 535 nm, respectively. It was suggested that these two absorption bands arise from an interaction between the two Cu ions (60). Two additional maxima are present at 359 nm and 785 nm (Fig.…”
Section: Recombinant Cu a Domain Of Synechocystis Cytochrome Cmentioning
confidence: 99%
“…Thus soluble subunit 11 fragments could be obtained which contained the Cu, site. As the hemes and Cu, are located in the membrane-bound portions, optical and EPR spectra of Cu,, unimpaired by other chromophores, could be obtained [24,[64][65][66]. By recombinant methods it also became possible to build Cu, sites into native proteins or fragments thereof [63, 67, 681.…”
Section: Progress Through Advances In Related Fields Protein Chem-mentioning
confidence: 99%
“…However, they also proposed a third bridging ligand, an oxygen species. The third paper [64] was mainly based on the theoretical evaluation by the method of complete neglect of differential overlapkpectroscopic of a model of the Cu, site. The Cu, site can be considered as being built up from two type 1 sites in which each Cu atom replaces a missing His on the other Cu atom.…”
Section: Relationship Of Cox To No Reductase (Nor) Of Pseudomonadsmentioning
confidence: 99%